Development of El- Student worksheet Integrated with Hidden Object Games Based on Predict-Observe-Explain Model to Improve Critical Thinking Skills and Visual Representation of High School Learners - Ana Helisa Rosianti; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the effectiveness of El- Student worksheet integrated hidden object games based on the POE model to improve the critical thinking skills and visual representation of high school students. This type of research is research and development (R&D). The development model is 4D (Define, Design, Development, and Disseminate). The trial subjects consisted of 94 students divided into three groups, the experimental, control 1 and control 2 class. Data collection consists of product validation sheets and critical thinking skills and visual representation tests. Student worksheet development software using Live worksheet. Data analysis used SBI for product feasibility and Multivariate Analysis of Variance test. The results showed that El- Student worksheet integrated hidden object game based on the POE model is feasible for physics learning. The average posttest score to improve the critical thinking skills and visual representation of the experimental class was 80.78 and 87.34, while the control class 1 was 79.26 and 79.84, and control class 2 was 79.54 and 76.83. The Multivariate Analysis of Variance test results shows a significant value of 0.000 which is smaller than 0.05 and almost 100% effective contribution. Thus, the product is declared effective for improving students' critical thinking skills visual representation.